Examination of theses on anatomy in the field of basic medical sciences (2016-2020) - Yunus Emre Kundakcı; Nadire Ünver (Genel Tıp Dergisi)
Objective: The aim of this study was to reveal descriptive data about postgraduate theses on anatomy and to determine their general trends. Material and Methods: Between the years 2016-2020 National Thesis Center of basic medical sciences, published in the department of anatomy thesis full text of 390; each of the thesis, name, type, year of publication, systematic and topographical anatomy class, study design, keywords, the situation of receiving budget support, the academic advisor, the title, the author's gender, bachelor degree and the publication of a thesis at the University of recorded and investigated. Frequency and percentage values were used for descriptive statistics and categorical variables. Results: Of the thesis, 237 (60.8%) were written by women, 242 (62.1%) were master's theses, 254 (65.1%) thesis advisor were professor, 113 (29%) received budget support, and 169 (43.3%) used radiological methods. The bachelor degree of the thesis authors was ranked as physiotherapy and rehabilitation (n=167, 42.8%), biology (n=64, 16.4%), nursing (n=58, 14.9%) and medicine (n=57, 14.6%). Of the thesis, 126 (32.3%) were from the head region and 174 (44.9%) were from the movement system. The most used keywords; computed tomography (n=58), morphometry (n=41), anthropometry (n=30), anatomy (n=27) and magnetic resonance imaging (n=25) were detected. Conclusion: In this study, bibliometric data about theses on anatomy were invastigated and a wide range of information was presented to the researchers in anatomy field. In recent years, it has been seen that female researchers and physiotherapists have come to the fore in anatomy postgraduate education. It can be said that especially studies involving the movement and nervous system or the head, lower and upper extremities attract the attention of researchers. In addition, radiological, experimental animal and anthropometric methods are frequently used in study designs. The result of the study is expected to shed light on anatomy graduate students, clinicians and researchers who carry out/will carry out their academic study.